2020
DOI: 10.1111/jop.13055
|View full text |Cite
|
Sign up to set email alerts
|

The tumor immune microenvironment and its implications for clinical outcome in patients with oropharyngeal squamous cell carcinoma

Abstract: Background: We examined PD-L1 expression on tumor cells (TCs) and immune cells (ICs) and density of CD3 + and CD8 + tumor-infiltrating lymphocytes (TILs) in patients with oropharyngeal squamous cell carcinoma (OPSCC) and investigated their significance on clinicopathological characteristics and clinical outcomes. Methods: In a cohort of 65 patients treated by definitive intensity-modulated radiotherapy (IMRT) with curative intent, immunohistochemical analysis of PD-L1 expression on TCs and ICs, and TIL subtypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The results revealed that positive PD-L1 expression was related to a significantly improved OS in patients with OPSCC (sHR = 0.63, 95% CI: 0.50-0.79). Differently, only seven articles provided HRs and 95% CIs for PFS in OPSCC ( 17 , 20 23 , 25 , 29 ). As depicted in Figure 2B , there was no significant heterogeneity among these 7 articles ( I 2 = 0%; p = 0.45).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results revealed that positive PD-L1 expression was related to a significantly improved OS in patients with OPSCC (sHR = 0.63, 95% CI: 0.50-0.79). Differently, only seven articles provided HRs and 95% CIs for PFS in OPSCC ( 17 , 20 23 , 25 , 29 ). As depicted in Figure 2B , there was no significant heterogeneity among these 7 articles ( I 2 = 0%; p = 0.45).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis indicated that positive PD-L1 expression was related to greater PFS in patients with OPSCC (sHR = 0.62, 95% CI: 0.49–0.79). Finally, the association between PD-L1 expression and LRC was investigated in four studies ( 22 , 23 , 29 , 32 ) and a significant heterogeneity was not detected among them ( I 2 = 48%; p = 0.12) ( Figure 2C ). Although a significant relationship did not emerged, results showed that LRC was improved in OPSCC patients that were PD-L1 positive (sHR = 0.92, 95% CI: 0.55–1.53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a highly significant correlation was seen between RanBP17 and CDKN2A , the gene encoding the cell cycle inhibitor and HPV surrogate marker p16 INK4A . Since HPV+ HNSCC are frequently associated with high levels of tumor infiltrating leukocytes (TILs) [ 24 ], the observed RanBP17 overexpression could also be derived from TILs present in the tumor. To further evaluate this aspect, we first looked into T-cell and B-cell marker expression levels and, consistent with previous reports, could observe significantly higher levels of these markers in HPV+ HNSCC compared with HPV- HNSCC (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports highlighted that HNSCC tumor microenvironment can regulate tumor response to radiation therapy throughout a crosstalk between tumor cells and the tumor microenvironment ( 190 ). Accordingly, it has been reported that miR-9 found enriched in HPV positive HNSCC exosome were able to enter into the macrophages inducing M1 macrophage polarization via downregulation of PPARδ, a member of the ligand-activated nuclear receptor superfamily involved in inflammation and innate immunity ( 191 ).…”
Section: Extracellular Micrornas As Biomarkers Of Hnscc Diagnosis and Prognosismentioning
confidence: 99%